1990
DOI: 10.1080/00913847.1990.11710022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity and Inactivity on Aerobic Power in Older Men (A Longitudinal Study)

Abstract: In brief To assess the decline in maximal aerobic power (V O2max) with age, two groups of men were studied: Fifteen exercisers were followed from age 45 to 68, and 15 controls were measured while training at age 52 and again at age 70 after being detrained for 18 years. Resting blood pressure of 120/78 was unchanged in the exercisers but rose from 135/85 to 150/90 in the nonexercisers. V O2max measured by open circuitry declined 13% in the exercisers from 44.4 to 38.6 ml-min(-1)-kg(-1); in the nonexercisers it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 13 publications
1
24
0
1
Order By: Relevance
“…The exercise only group maintained their weight loss during the second year. The longitudinal research published by Kasch and associates 41 support the effect of habitual physical activity on weight control. They reported that the 25 y longitudinal weight loss of physically active men was 3.4 kg (70.14 kgay), while their sample of inactive men gained 3.2 kg (0.13 kgay).…”
Section: Discussionmentioning
confidence: 98%
“…The exercise only group maintained their weight loss during the second year. The longitudinal research published by Kasch and associates 41 support the effect of habitual physical activity on weight control. They reported that the 25 y longitudinal weight loss of physically active men was 3.4 kg (70.14 kgay), while their sample of inactive men gained 3.2 kg (0.13 kgay).…”
Section: Discussionmentioning
confidence: 98%
“…O 2 peak can be improved with exercise training of sufficient duration, frequency, and intensity (15,17,18,34,42,43). The increase in V…”
Section: Discussionmentioning
confidence: 99%
“…Even so, variation in aerobic capacity is large enough that the range in older adults overlaps that of younger adults (55,62,72). Absolute rates of decline are higher in sedentary adults than active adults (23,37,57). A recent study estimated that exercising adults lose 0.25 mUkg/min in aerobic capacity each year, which is one-third the yearly loss rate of 0.711mVkg/min for nonexercisers (57).…”
Section: Age-related Declinementioning
confidence: 99%
“…Much attention has been paid in gerontology to the decline in aerobic capacity with age (13,20,37,57,83). Between the ages of 30 and 80, about 50% of aerobic capacity is lost.…”
Section: Age-related Declinementioning
confidence: 99%